If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(6x + -5) = 18x + 15x Reorder the terms: 3(-5 + 6x) = 18x + 15x (-5 * 3 + 6x * 3) = 18x + 15x (-15 + 18x) = 18x + 15x Combine like terms: 18x + 15x = 33x -15 + 18x = 33x Solving -15 + 18x = 33x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-33x' to each side of the equation. -15 + 18x + -33x = 33x + -33x Combine like terms: 18x + -33x = -15x -15 + -15x = 33x + -33x Combine like terms: 33x + -33x = 0 -15 + -15x = 0 Add '15' to each side of the equation. -15 + 15 + -15x = 0 + 15 Combine like terms: -15 + 15 = 0 0 + -15x = 0 + 15 -15x = 0 + 15 Combine like terms: 0 + 15 = 15 -15x = 15 Divide each side by '-15'. x = -1 Simplifying x = -1
| b/17=-13 | | 4(x-30)+5x=-48 | | x+(1+x)+(2+x)=228 | | 5r-4r=16 | | -8(9h-5)=-17 | | -12+4n=4 | | -11+b=-3 | | 19a-12-4a=(-57) | | (Y6/Y3)4 | | k/18=-4 | | 393=17n+2 | | 13=11-y | | m/15=16 | | -6x-10=-16 | | -5d-24=4(1d+6)-1d | | 6x+21=6x+24-3 | | 2(2z-3)-2(4-5z)=2 | | -50x^10/10x^5 | | -5-3x=25 | | 2m-8=6 | | 3a^2+10=0 | | 5x(x-3)+6=5x-9 | | m+-1=9 | | 6x+6.32=2x+14 | | -5s-16=-4s | | -(4/x-4)=5 | | 9-5n=39 | | 16i+5=3oi-2 | | .5x+8.5-15=-3 | | 5y+5=4z+9 | | 1.33t-8=-12 | | x+17477=1345676543427 |